Interview with Michael Löwy (CNRS): Russian literature, philosophy and messianism - Jimmy Sudário Cabral (RUS (São Paulo), 2021)
In the history of the Dostoevsky’s and Tolstoy’s reception in modern philosophical thought, a philosophical tradition of German-Jewish origin has a prominent role. Product of a singular “spiritual synthesis”, as observed by Michael Löwy, the thought of Franz Kafka, George Lukács, Ernst Bloch, and Walter Benjamin has appeared in modern times as the sign of messianic claim for a libertarian, radical, and revolutionary socialism. Bearing in common the experience of not being reconciled with the world and history, this generation of intellectuals from Central Europe had “Jewish messianism” and “German romanticism” as privileged sources of their world-view. The religious concept of redemption and the political notion of libertarian utopia were combined in the trajectory of this German-Jewish intelligentsia that promoted an unprecedented reconfiguration of philosophical thought. It is well-known that the works of Dostoevsky and Tolstoy traverse the messianic and utopian imagery of this generation of revolutionary intellectuals and, as professor Michael Löwy assertively stated, “the utopian Bloch finds in Dostoevsky elements that legitimize The Principle of Hope: Aliocha Karamazov would be a precursor to the ‘religious kingdom of justice’…”. Such an observation is at the heart of a critical fortune accumulated in the works of Löwy and opens paths of analysis that have yet to be made in relation to the reception of Russian literature in modern Jewish philosophy.